On the nature of sources of pulsating radiation in weakly inverted media - Kirichok, A.V.; Kuklin, V.M.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2015)
The conditions for the occurrence of a periodic sequence of pulses of coherent radiation in a weakly inverted two-level medium are investigated. It is studied the dependence of the pulse period and amplitude on the inversion pumping levelandradiation losses. It is shown that an increase in the size of the radiating system leads to the growth of the total radiation intensity and the pulse repetition period. This dependence is consistent qualitatively with the observedcharacteristics of the cosmic sources of pulsed radiation. Розглянуто умови виникнення періодичної послідовності імпульсів когерентного випромінювання в слабоінвертованому дворівневому середовищі. Досліджено залежність періоду і амплітуди виникаючих імпульсів від рівня накачки інверсії та радіаційних витрат. Показано, що зі збільшенням розмірів випромінюючої системи зростає інтегральна інтенсивність випромінювання і збільшується період генерації імпульсів. Така залежність якісно збігається з характеристиками космічних джерел пульсуючого випромінювання. Рассмотрены условия возникновения периодической последовательности импульсов когерентного излучения в слабоинвертированной двухуровневой среде. Изучена зависимость периода и амплитуды возникающих импульсов от уровня накачки инверсии и радиационных потерь. Показано, что с увеличением размеров излучающей системы растет интегральная интенсивность излучения и увеличивается период генерации импульсов. Такая зависимость качественно совпадает с наблюдаемыми характеристиками космических источников пульсирующего излучения.